Application of gamma-ray computed tomography for the analysis of gas holdup distributions in centrifugal pumps. (December 2015) - Schäfer, Thomas; Bieberle, André; Neumann, Martin; Hampel, Uwe
Abstract: In this work, gas–liquid distributions in an industrial centrifugal pump operated at various steady state conditions have been quantitatively determined. Therefore, high-resolution gamma-ray computed tomography (HireCT) has been applied, operated in time-averaging rotation-synchronized CT scanning mode. Detailed studies have been performed on a hydraulic test facility providing authentic operating conditions for industrial centrifugal pumps. The gas phase distribution in the centrifugal pump has been studied for swirling gas–liquid two-phase flow as an inlet flow regime and at defined inlet gas volumetric flow rates between 0% and 5%. In this way, the influence of the inlet flow boundary conditions on the performance of the centrifugal pump as well as the gas holdup distribution within the impeller region could be successfully determined. Graphical abstract: Highlights: Quantitative two-phase flow investigations in an industrial centrifugal pump Swirling gas-liquid two-phase flow inlet regime with central formed gas core Influence of inlet gas fraction on gas holdup distributions inside the impeller Application of rotation-synchronized high-resolution gamma-ray computed tomography Specific accumulations of gas inside the impeller chambers have been discovered.